Assessing Intangible Value: The Mediating Roles of WOM and Brand Credibility in Quality and Equity Nexus in Emerging Market - Oppong, Peter Kwasi; Maama, Haruna (International Review of Management and Marketing, 2025)
There is a growing demand for herbal treatments, which has resulted in intensified competition in the emerging herbal market. The increasing competition has compelled firms to build strong brand equity to sustain profitability and differentiation. However, the mechanisms through which brand quality, word-of-mouth (WOM), and brand credibility interact to influence brand equity remain underexplored, particularly in the herbal industry. The research aims to examine the mediating role of WOM on the extent to which brand quality influences credibility and equity in an emerging herbal market. The data for this paper were gathered from 226 customers through systematic random procedures. Structural equation modelling was utilised to test the hypotheses via AMOS 24. The findings demonstrate that WOM plays a complete intervening role in the link between brand quality and equity, and also partially mediates in the brand quality and credibility nexus. The analysis also indicates that brand credibility completely intervenes in the nexus between WOM and equity. The study establishes that WOM is an important factor if herbal companies want to create brand quality to strengthen brand credibility and equity, whilst credibility is regarded as a critical ingredient when utilising WOM to raise brand equity in the emerging market.